2009
DOI: 10.1002/chem.200801146
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structural Complexities of Metal–Metalloid Nanoparticles: The Case of Ni⋅B as Catalyst

Abstract: Understanding of the structural complexities of metal-metalloid nanoparticles is at the heart of several proposals for investigating the physical properties and practical applications of these bi-elemental nanomaterials. To date, the most widely studied metal-metalloid is the nickel-boron (Ni.B) system; however, the exact nature of the structure of the material itself has remained unclear. Herein we show our systematic investigations of the material in an attempt to reveal its fascinating nanostructure. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
7
32
0
Order By: Relevance
“…Only broad diffractions are observed. This is in accord with the literature reports of the metal-boron nanoparticles [54].…”
Section: Morphology Of Pdenieb Nanoclusters In Hydrogelssupporting
confidence: 93%
See 2 more Smart Citations
“…Only broad diffractions are observed. This is in accord with the literature reports of the metal-boron nanoparticles [54].…”
Section: Morphology Of Pdenieb Nanoclusters In Hydrogelssupporting
confidence: 93%
“…The NieB particles are prone to aggregate in micrometer-sized assemblies in solution. The catalyst surface is known to have both Ni(0) and boron in a mixture of oxidation states (0/þ3) [54]. In order to prevent aggregation, poly(N-vinylpyrrolidone) (PVP) was added in the solution during reduction of Ni salts in this study.…”
Section: Morphology Of Pdenieb Nanoclusters In Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that one relatively broad dispersing peak appears near 2Â ≈ 45 • for the Ni-Co-B catalyst heated at 373 K, indicating an amorphous structure. Furthermore, according to a previous study, Geng et al [24] used high-resolution transmission electron microscopy (HRTEM) to observe the ultrafine crystalline structure of a Ni·B catalyst, and found that although the component nanoparticles are extremely small, they are nevertheless crystalline. Based on this point of view, here the Ni-Co-B catalysts may also have tiny Ni and Co crystallites bound in the matrix of boron-containing species.…”
Section: Hydrogen Generating Testmentioning
confidence: 99%
“…On the other hand, these catalytic species need to be stabilized on the alumina under high temperature conditions. 19,20 Therefore, the development of Ni-B is highly desirable. Ni-B has been widely studied in electroless nickel deposition owing to its high activity, good selectivity and strong sulfur poison resistance, as well as its environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%